CHARACERISTICS OF DIABETIC PERIPHERAL NEUROPATIC - SUYANTO SUYANTO (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
Introduction: Diabetes Mellitus (DM) for a long time may experience diabetic peripheral neuropathy (DPN). This study aims to determine the characteristics of diabetic peripheral neuropathy. Methodology: descriptive analytic design with cross sectional design used with 35 samples obtained with purposive sampling technique. The sample of the research was diabetic peripheral neuropathy patients with maximum leg sensitivity score 8. Results: The frequency distribution test results showed the average age of respondents 49.5 ± 6.7, female gender (68.4%), diabetes mellitus 4.6 ± 2, dominant pharmacological treatment of Oral Hypoglycemic Drugs (OHO) (84.1%) and average ABI values 0.85 ± 0.05, mean foot sensation score of 8 ± 0.8. Discussion: the characteristics of patients with diabetic peripheral neuropathy are very diverse, it is necessary to see the correlation between characteristics with the incidence of diabetic peripheral neuropathy.